Intravenous DOPG liposomes do not augment pH gradient liposome supported peritoneal dialysis in treatment of acute intravenous amitriptyline intoxication in rats. Issue 1 (1st January 2018) - Cave, Grant; Harvey, Martyn; Pianca, Natasha; Robertson, Ivan; Sleigh, Jamie; Wu, Zimei
Abstract: Introduction : Liposomes are nanospheres of lipid bilayer which can bind drug either in the phospholipid membrane or in the central aqueous droplet. Liposomes loaded with a drug can facilitate drug delivery, and empty liposomes can sequester certain drugs to reduce aqueous drug concentrations in experimental intoxication. Therapeutic dialysis in intoxication is limited by drug volumes of distribution and blood protein binding. In rats intoxicated with intravenous amitriptyline, we examined adding intravenous membrane-binding 1, 2-dioleoyl-sn-glycero-3-phosphoglycerol (DOPG) liposomes to liposome supported peritoneal dialysis (LSPD) in which liposomes in dialysate were augmented with an acidic core. The hypothesis was that a "gradient of liposome affinity" would increase LSPD amitriptyline concentrations. Methods : Seven control and five intravenous DOPG liposome pre-treated rats were injected with amitriptyline, followed 10 min later by a 10-min LSPD dwell. Results : DOPG liposomes increased blood amitriptyline concentrations by 50%; control (median [IQR] 1250 [951–1356] nmol/L; intravenous DOPG 1702 [1602–1864] nmol/L, p = 0.032). However, there was no corresponding increase in LSPD dialysate amitriptyline concentrations at the end of the dwell; control (median [IQR] 430 [334–2180] nmol/l, intravenous DOPG 414 [387–483] nmol/L p = 0.75). Conclusions : Pre-treatment with DOPG liposomes decreased amitriptyline volume of distribution but had no significant effect on elimination of amitriptyline by LSPD.